Literature Study: Implementation of an Adaptive Curriculum for Students with Special Needs in Inclusive Schools - Ana Rafikayati; Reza Akbar Fauzan; Eryana Fatimasari Retno Budiati; Budiyanto Budiyanto; Endang Pudjiastuti Sartinah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study reviews how adaptive curricula are implemented for students with special needs in inclusive schools and identifies dominant strategies, challenges, and enabling factors. Using a systematic literature review approach, the study screened 100 publications from Google Scholar, selected 40 for abstract and title relevance, and analyzed 20 articles published between 2020 and 2025. The synthesis shows that inclusive schools generally still rely on the national curriculum, while adaptation is carried out through accommodation and modification strategies such as escalation, duplication, substitution, and omission. Effective implementation depends on teacher competence, school leadership, parental involvement, and available resources. However, limited training, inadequate infrastructure, and weak cross-stakeholder coordination remain persistent barriers. The findings suggest that an adaptive curriculum is not merely a technical adjustment but a central mechanism for ensuring equitable participation and meaningful learning outcomes for students with special needs in inclusive settings. This review offers practical implications for teachers, school leaders, and policymakers in strengthening inclusive education.